An Evaluation on the Impact of Ergonomic Office Layout to the Workers Productivity: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ergonomic Layout is one of the major influences on workers’ productivity; it can besignificantly impacted by the layout of their workspaces and the equipment they use at work.Additionally, the layout and design of the workspace are essential for fostering inspiration,which has a positive impact on their job. The employees mustn't experience tiredness anddiscomfort since it can increase employee involvement. Employees must feel calm andrelaxed to improve workplace productivity. Researchers were interested in knowing theimpact of the Ergonomic Layout on Workers' Productivity.The leading findings are that most respondents are female from 25-30 years old, and mostof them are Master’s Degree Holder. The main problem that researchers encountered is thatemployee should never compromise their health and bodily safety to complete a job. Theemployees must concentrate in a peaceful and quiet environment and rank in Strongly Agreeas recommended offices should have comfortable chairs to support the spine of theiremployees and provide good lighting to reduce strain and avoid craning the neck. They mustconsider ergonomic efficiency posture, morale reinforces health, and provide guidance ontheir safe work procedures. Lastly, good relations with employees result from satisfaction.Based on the findings, researchers gathered to come up to the conclusion that the successof the organization is very much dependent on how its employees perform at the workplaceand the respondents strongly agreed. Though the researchers desire to recommend to thedepartment head that they should provide good lighting and high-quality equipment, shouldprovide a monthly check-up for their safety and health, and have a wide space to moveemployees properly and not be crowded.
Keywords: Business Administration